The Need For Hardworking In Order To Be Successful In Gabriele Muccino's The Pursuit Of Happyness: An Individual Psychological Perspective - Mustafalia, Azizah (2012)
The problem of this study is to reveal how hardworking of the major character in order to be successful in Gabriele Muccino's the Pursuit of Happyness movie which is viewed from individual psychological perspective. The objectives of the research are to analyze the movie based on the individual psychological perspective. This research paper belongs to the qualitative research. The object of the study is the hardworking of Chris Gardner as the major character in the Pursuit of Happyness movie. The data source comes from primary data source that is the Pursuit of Happyness movie and the secondary data sources are other sources related to the movie. The method of data analysis used in this study is descriptive analysis. From the result of analysis, it can be drawn some conclusions. First, based on the structural elements of movie, it is clear that in this movie, Muccino delive rs a message that there is a way when there is a will. Second, based on the a psychological analysis, the Pursuit of Happyness director, Gabriele Muccino, illustrates individual psychological phenomenon in which the major character always works hard to achieve his goal of life